Determinación de factores de patogenicidad en cepas Campylobacter jejuni y Campylobacter coli quinolonaresistentes provenientes de animales de corte (bovinos y cerdos) y caninos de la ciudad de Loja - Bravo Torres, Domenica Michelle (2018)
Abstract: The Campylobacter species, mainly Campylobacter jejuni and Campylobacter coli are the major cause of gastroenteritis in developed countries and the second or third in developing countries, the disease is transmitted from the consumption of foods of animal origin that are contaminated by these species. Currently, virulence factors have been identified related to the infection in the gastrointestinal tract of animals and humans; These factors are motility due to the presence of flagella, the capacity of adherence and invasion of cells and the production of cytotoxins. This thesis determined the adhesion capacity in strains of C. jejuni and C. coli, by using the HEp-2 cell line, 22 isolated samples of cattle, pigs and dogs were analyzed in the city of Loja; the results, allow to determine that a strain of C. coli from cattle had a higher percentage of adherence (31.5%), considering it a positive strain for this mechanism according to the criterion established, in C. jejuni no positive results were found this adhesion capacity.